Enantiomeric separation of [60]fullerene derivatives with an inherent chiral addition pattern - Gross, Birgit; Schurig, V.; Lamparth, Iris; Herzog, Andrea; Djojo, Francis; Hirsch, Andreas (Chemical Communications, 1997)
Enantiomeric separation of bis-, tris- and hexakis-adducts of [60]fullerene with achiral addends and an inherent chiral addition pattern is achieved by HPLC using a chiral Whelk-O1 phase.